Gas exchange threshold and VO2max testing for athletes: An update - Pettitt, R. W.; Clark, I. E.; Ebner, S. M.; Sedgeman, D. T.; Murray, S. R. (The Journal of Strength and Conditioning Research, 2013)
Standardized graded exercise test (GXT) protocols are ineffective for testing endurance athletes. Scientists have called for the abandonment of traditional techniques for corroborating "true" maximum oxygen uptake (VO2max), as measured during a GXT. Instead, a new technique, the verification bout subsequent to the GXT, has emerged for establishing the "true" VO2max. The addition of the verification bout reframes how the GXT should be viewed. In this article, we summarize the methods for developing custom GXT protocols, identifying threshold and interpolating power or outdoor running velocity, and implicating the verification bout.